Persepsi Guru Penggerak dalam Penerapan Kurikulum Merdeka di Sekolah Menengah Pertama Kabupaten Rokan Hilir - Oktariza, Nabilla; Zen, Zelhendri; Syafril, Syafril; Pratiwi, Rahmi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The background of this research problem is limited access to technology, inadequate facilities, and infrastructure, as well as a lack of managerial support that can affect the effectiveness of curriculum implementation. This study aims to analyze the perception of Driving Teachers regarding the implementation of the Independent Curriculum, focusing on the obstacles they face in the learning process. The method used in this study is quantitative with a descriptive approach, using a questionnaire as a data collection instrument. The data analysis technique uses descriptive analysis of all research data. The results of the study showed that most respondents had a good understanding of the Independent Curriculum, with the respondents' achievement rate reaching 93.38%. However, challenges such as limited internet connections, low understanding of technology, and limited time allocation for the implementation of the Pancasila Student Profile Strengthening Project (P5) can hinder the success of the curriculum. This research is expected to provide recommendations to increase support for Teacher Mobilizers and improve learning conditions in similar areas.